Create Stunning Scenes in Blender LiveLessons Techniques for Modeling and Rendering 3D Images - Villar, Oliver (Addison-Wesley Professional, 2018)
17+ Hours of Video Instruction Take your 3D skills to the next level and explore what you can achieve with Blender Creating Stunning Scenes in Blender LiveLessons teaches you the entire process needed to turn your ideas into impressive 3D scenes using Blender, the best open source and free 3D creation suite. After you know the basics, this course will take your skills to a whole new level. Description This video training takes you through the entire process of organizing, modeling, texturing, lighting, rendering, and compositing a scene in Blender, the popular open source and free 3D-creation suite. This course shows different techniques and explains not only how to use them, but why they can be useful in different situations. Step-by-step screencast videos guide the viewer through the entire process. After watching this course, artists will know how to take a scene from a concept or idea to its finished result and use different modeling and texturing methods, each of which can be useful for the creation of different types of objects. They'll also know how to light and render a scene to achieve realistic looking images. On top of that, viewers will be able to use techniques to work in teams, like scene and objects linking, so various people can simultaneously work on the same scene. About the Instructor Oliver Villar is a Spanish digital artist with more than 10 years of experience. In 2010, he discovered his passion for teaching, and he's funded blendtuts.com and blendtuts.es, which are sibling websites where he teaches 3D design online for English and Spanish audiences. He's a Blender Foundation Certified Trainer and author of the book Learning Blender: A Hands-On Guide for Creating 3D Animated Characters . After years working as a freelancer and for companies, Oliver is now fully dedicated to the creation of educational content, currently working as the co-director of Luke's Escape, a 3D animated short film, created with Blender in collaboration with an international team. Skill Level Intermediate Learn How To Create a complete 3D scene from start to finish Successfully plan the creation process Use linked libraries to have an efficient workflow Use different techniques to model, unwrap, texture, and shade a set of objects Light, render, and composite a scene to achieve a beautiful result Who Should Take This Course People who are familiar with the basics of Blender, but want to learn the full 3D-creation process and improve their skills. ...